Learning from COVID-19 experience: a study amongst ENT surgeons’ COVID behaviour - Bhavana, Kranti; Soni, Sweta; Sharma, Bhartendu Bharti; Chaudhary, Neha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Health care services across the world have undergone several modifications in view of ongoing COVID-19 pandemic. Otolaryngology needs special mention in this context owing to its proximity to virus’s natural habitat. Various ENT procedures are significantly aerosol generating and hence appropriate precautions and procedural modifications are needed. We aimed to determine attitude and practices of ENT professionals during COVID-19 pandemic and their level of preparedness towards resuming practice, teaching and training activities. Methods: We conducted an online survey through Google forms, participants were asked to fill up a multiple choice questionnaire. Responses collected were analysed and interpretations made on basis of most favoured options. Results: Majority of respondents was aware of the potential risks and precautions to be taken during Outpatient and surgical procedures and was willing to adapt their clinical setups to protect themselves and their patients. Few of them wanted to follow stricter protocols like doing endoscopies for therapeutic purposes only, using a PAPR for lengthy surgeries, not allowing trainees to assist in surgeries etc. Conclusions: We concluded that fresh guidelines are needed taking in account the opinion of government and private practitioners, with provisions for continuing training activities.